Sociodemographic determinants and violence against women. Tacna Peru: a retrospective analysis of the data of the women emergency center - Choque-Chura, Olga (2019)
Objective. To determine the relationship of sociodemographic determinants and violence against women. Tacna 2015-2017. Material and methods. Cross-sectional study, with a sample of 1945 cases that filed a complaint. Statistical analysis used the square, O.R. (prevalence ratio) for analysis of the associated determinants, considering a significant p-value <0.05. Results. Psychological violence is the most prevalent. The sociodemographic determinants of the assault associated with psychological and physical violence were: age, marital status, educational level and status of paid work. The determinants of the assault associated with sexual violence are: age (most vulnerable <19 years). The determinants of the aggressor associated with psychological violence were: age and sex, with women being the ones who mostly carry out this type of violence; The determinants of the aggressor associated with physical violence: intermediate ages and coexistence. The determinants associated with sexual violence are: age, sex and living with the victim, with a value p = <0.001 for most of these associations. Conclusions. According to the sociodemographic determinants of the assault, the older people are at greater risk of psychological violence, ages between 20 and 49 years are at higher risk of physical violence, <19 years are at higher risk of sexual violence. Having paid work increases the risk of violence. The predominant determinants of the aggressor are: age with similar characteristics for psychological, physical and sexual violence than in women, with evidence that the woman aggravates another woman.